Pengaruh Kualitas Pelayanan, Lokasi Dan Emosional Terhadap Loyalitas Konsumen Pada Bank Kaltim Cabang Balikpapan - Tirsa Tivnirini Taroreh; Joko Sabtohadi; Mariani Madjid (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:The objectives and benefits of this study are:1.      To prove whether service quality is together,location, and emotional has a significant influence on consumer loyalty at Balikpapan's Kaltim Bank Branch.2.      To prove where individually between service quality, location, and emotional has a dominant influence on customer loyalty at Balikpapan's Kaltim Bank Branch.The results of this study are expected to be used as an evaluation forBalikpapan Bank Kaltim Branch which can be used as a material consideration to improve management performance to take the right marketing strategy in the future competition.Based on the results of the analysis and discussion conducted in the previous chapter, some conclusions can be drawn as follows:Allegations stating, it is alleged that together service quality, location, and emotional have a significant influence on customer loyalty at the proven Balikpapan Branch of Bank Kaltim. With a calculated F value of 24.942 greater than F table or F0.05 of 2.70 and a significance value of 0.000 is smaller than the significance level = 0.05, then the first hypothesis in this study is acceptable.Allegations stating that it is assumed that individually the location has a dominant influence on customer loyalty at the proven Balikpapan Branch of Bank Kaltim. With the value of t count of 4.705> t table of 1.66088 and a significance value of 0.000 is smaller than the significance level = 0.05, then the first hypothesis in this study is acceptable.                Keywords: Services Quality, Locations, Emotional And Consumer Loyalty